Dinâmica relativista. Fisica e filosofía - Meneses, Ramiro Délio Borges de (ENDOXA, 2007)
Energy and mass are generally interpreted as difFerent properties of matter, for instance: the energy of a particle ¡s generally interpreted as a measure of its capacity to do work. The law of the equivalence of mass and energy does not imply that mass is sometimes converted into energy or vice versa, but states that the changes in ene are accompanied by corresponding changes in the other, inertial mass and energy being proportional to each other; E = m • c . The law of conservation of mass is, therefore, equivalent to the law of conservation of energy and they are sometimes combined together and called the law of conservation of mass-energy. The proportionality between the relativistic mass and energy leads to the fact that the statement on the conservation of the total relativistic mass of particles is the statement on the conservation of the total energy using the relation between the relativistic mass and energy. Accordingly we can analyse the philosophical reasons of the relativistic dynamic. But this examination implicates a review on the causality principie, because we aspire to the new philosophical contained for the relativistic arguments.